Demonstration and Characterization of the Cell Wall Carbohydrate and Protein Antigens from Clostridium Botulinum Type E Saroma - Takumi, Kemji; Nagao, Shigeki; Takeoka, Aya (MICROBIOLOGY and IMMUNOLOGY, 1991)
Two different cell wall antigens, carbohydrate (CHO) and protein (P), from Clostridium botulinum type E Saroma were extracted with sodium dodecyl sulfate (SDS) and purified by chromatography on DEAE-Sepharose CL-6B and Sephadex G-75 or G-100. The CHO antigen was composed of glucose, galactose, glucosamine, galactosamine, alanine and phosphorus with a molar ratio of 1.5:1.5:0.25:0.25: 1:1. The P antigen was an acidic protein with a molecular weight of 60kDa, in which the major amino acids were aspartate, glutamate and serine, while the minor ones were cysteine and methionine. Thin sections of the intact or SDS-extracted cells of the organism demonstrated that the cell wall was composed of a two-layered structure, an inner layer about 20nm thick and an outer layer about 10nm, and by the extraction with SDS, the outer layer disappeared from the cell surface, leaving the inner layer. Immunogel diffusion tests demonstrated that either CHO antigen or P antigen was common among the nonproteolytic strains of C. botulinum.